Serotonin (5-HT) neuron-specific inactivation of Cadherin-13 impacts 5-HT system formation and cognitive function. (15th May 2020) - Forero, Andrea; Ku, Hsing-Ping; Malpartida, Ana Belén; Wäldchen, Sina; Alhama-Riba, Judit; Kulka, Christina; Aboagye, Benjamin; Norton, William H.J.; Young, Andrew M.J.; Ding, Yu-Qiang; Blum, Robert; Sauer, Markus; et al.
Abstract: Genome-wide screening approaches identified the cell adhesion molecule Cadherin-13 (CDH13) as a risk factor for neurodevelopmental disorders, nevertheless the contribution of CDH13 to the disease mechanism remains obscure. CDH13 is involved in neurite outgrowth and axon guidance during early brain development and we previously provided evidence that constitutive CDH13 deficiency influences the formation of the raphe serotonin (5-HT) system by modifying neuron-radial glia interaction. Here, we dissect the specific impact of CDH13 on 5-HT system development and function using a 5-HT neuron-specific Cdh13 knockout mouse model (conditional Cdh13 knockout, Cdh13 cKO). Our results show that exclusive inactivation of CDH13 in 5-HT neurons selectively increases 5-HT neuron density in the embryonic dorsal raphe, with persistence into adulthood, and serotonergic innervation of the developing prefrontal cortex. At the behavioral level, adult Cdh13 cKO mice display delayed acquisition of several learning tasks and a subtle impulsive-like phenotype, with decreased latency in a sociability paradigm alongside with deficits in visuospatial memory. Anxiety-related traits were not observed in Cdh13 cKO mice. Our findings further support the critical role of CDH13 in the development of dorsal raphe 5-HT circuitries, a mechanism that may underlie specific clinical features observed in neurodevelopmental disorders. Highlights: Exclusive inactivation of CDH13 in 5-HT neurons increases 5-HT neuron density in the embryonic and adult dorsal raphe. Conditional deletion of CDH13 also increases serotonergic innervation of cortical regions in the mouse embryonic brain. Adult Cdh13 cKO mice display delayed acquisition of several learning tasks and a subtle impulsive-like phenotype.